2019
DOI: 10.3390/app9193962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Fluence and Pulse Overlap on Machining of Microchannels in Alumina Ceramics Using an Nd:YAG Laser

Abstract: The quality of micro-features in various technologies is mostly affected by the choice of the micro-fabrication technique, which in turn results in several limitations with regard to materials, productivity, and cost. Laser beam micro-machining has a distinct edge over other non-traditional methods in terms of material choices, precision, shape complexity, and surface integrity. This study investigates the effect of laser fluence and pulse overlap while developing microchannels in alumina ceramic using an neod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Figure 7 shows the contact resistivity with The next important parameter was laser speed, which was determined based on the X-Y stage motion speed. Reducing the laser speed increases the percentage of overlap among laser pulses, which can be expressed as 1 − V f ×D × 100, where V is the laser scan speed, which was 10, 40, and 70 mm/s; f (Hz) is the pulse frequency; and D (mm) is the laser spot size [14]. A green laser beam with a spot size and frequency of approximately 0.025 mm and 500 kHz, respectively, was used at various laser speeds ranging from 10 (99.92% overlap) to 70 mm/s (99.44% overlap).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows the contact resistivity with The next important parameter was laser speed, which was determined based on the X-Y stage motion speed. Reducing the laser speed increases the percentage of overlap among laser pulses, which can be expressed as 1 − V f ×D × 100, where V is the laser scan speed, which was 10, 40, and 70 mm/s; f (Hz) is the pulse frequency; and D (mm) is the laser spot size [14]. A green laser beam with a spot size and frequency of approximately 0.025 mm and 500 kHz, respectively, was used at various laser speeds ranging from 10 (99.92% overlap) to 70 mm/s (99.44% overlap).…”
Section: Resultsmentioning
confidence: 99%
“…Lamp current intensity is the primary parameter in laser machining. Some researchers, such as Liu et al [ 67 ] and Li et al [ 68 ], used the lamp power, whereas some studies have reported the lamp current intensity as a primary laser parameter such as Vincent et al [ 69 ], Abdo et al [ 70 ], and Mohammed et al [ 71 ]. A laser source used in this study can deliver maximum power of 30 W by the utilization of 100% lamp current intensity.…”
Section: Methodsmentioning
confidence: 99%
“…As the layer thickness increased, the unit material required to be removed per laser scan increased, which was accomplished with increased laser intensity. The resultant higher molten metal eroded the side walls of the microchannels as it gets ejected out of the channel, resulting in tapered side walls of the microchannel [34]. Moreover, once some of the molten metal get adhere to the side walls, the laser loses the focus near the edges for the subsequent layers resulting in a tapered microchannel.…”
Section: Taper Anglementioning
confidence: 99%
“…It could be seen that as the scan speed and layer thickness increased, spatter thickness increased. The increase was in tapered side walls of the microchannel [34]. Moreover, once some of the molten metal get adhere to the side walls, the laser loses the focus near the edges for the subsequent layers resulting in a tapered microchannel.…”
Section: Spattermentioning
confidence: 99%